SIKAP GENERASI MUDA TERHADAP BAHASA BALI DI DESTINASI WISATA INTERNASIONAL BALI - Ni Luh Nyoman Seri Malini; Ida Bagus Putra Yadnya; Ni Luh Putu Laksminy; I Gst Ngurah Kt Sulibra (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This writing aims at investigating language attitude of Balinese young generation toward Balinesse, their mother tongue in tourist destination.   Qualitative approach is applied in this research. The data were in the form of spoken data, written data, and researcher’s language instuition. Through participative observation the data were collected from young generation at tourist destination such as Kuta, Sanur and Ubud by using questionnaire and observation sheet. The respondents were given 10 items of questions related to cognitive, affective, and behavioral (connative) aspects. Data collected were then analyzed by the theory of language attitude. The study reveals that there are positive attitudes towards Balinese language by young generation in international tourist destination in Bali